Relación entre el clima organizacional y la satisfacción laboral de los colaboradores del Colegio Particular San Agustín de Iquitos, octubre 2019 - Grandez Mavila, Jeffrey Alexander (2021)
Human resources are the most valuable asset for any organization, so it is necessary to know if you are satisfied working in the institution and what factors determine that satisfaction. The objective of the research was to determine the relationship between the organizational climate and the job satisfaction of the collaborators of the Colegio Particular San Agustín de Iquitos, in the period October 2019; carrying out this research of Quantitative type, Correlational level and Non-Experimental design. The research concludes that there is a direct relationship between the organizational climate and job satisfaction, because the Correlation Coefficient (r) was r = 0.942871931; value very close to +1. Similarly, 55.34% of the respondents rated the organizational climate in the educational institution as "Good". 63.11% of workers consider job satisfaction as "Good" and 24.47% as "Very Good". The statistical test that shows the association between the organizational climate and job satisfaction resulted in the Correlation Coefficient being r = 0.942871931; and the Determination Coefficient was R2 = 0.978937615; concluding that there is statistical significance between both variables. The worker's profile is that he is "Between 35 - 39 Years" (23.30%), is of the "Female" sex (58.25%), works in "Primary" (28.16%) and is "Satisfied" (63.11%) of working in the institution.